Increased expression of β-glucosidase A in Clostridium thermocellum 27405 significantly increases cellulase activity - Maki, Miranda L. (Landes Bioscience, 2013)
β-glucosidase A (bglA) in Clostridium thermocellum 27405 was increased by expression from shuttle vector pIBglA in attempts to increase cellulase activity and ethanol titer by lowering the end product inhibition of cellulase. Through a modified electrotransformation protocol C. thermocellum transformant (+MCbglA) harbouring pIBglA was produced. The β-glucosidase activity of +MCbglA was 2.3- and 1.6-fold greater than wild-type (WT) during late log and stationary phases of growth. Similarly, total cellulase activity of +MCbglA was shown to be 1.7-, 2.3- and 1.6-fold greater than WT during, log, late log and stationary phases of growth. However, there was no significant correlation found between increased cellulase activity and increased ethanol titers for +MCbglA compared with the WT. C. thermocellum has industrial potential for consolidated bioprocessing (CBP) to make a more cost effective production of biofuels; however, the hydrolysis rate of the strain is still hindered by end product inhibition. We successfully increased total cellulase activity by increased expression of bglA and thereby increased the productivity of C. thermocellum during the hydrolysis stage in CBP. Our work also lends insights into the complex metabolism of C. thermocellum for future improvement of this strain.